Xpert MTB/RIF performance to diagnose tuberculosis and rifampicin resistance in a reference centre in southern Brazil. Issue 3 (5th August 2019) - Feliciano, Cinara Silva; Menon, Lucas José Bazzo; Anselmo, Livia Maria Pala; Dippenaar, Anzaan; Warren, Robin Mark; Silva, Wilson Araújo; Bollela, Valdes Roberto
Effective treatment of tuberculosis (TB) remains a serious public health problem in many countries, including Brazil, especially when considering drug-resistant disease. Xpert MTB/RIF has been implemented in many countries to reduce the time to TB diagnosis and to rapidly detect rifampicin resistance. The study aimed to describe and evaluate Xpert MTB/RIF performance in diagnosing pulmonary TB and rifampicin resistance in a tertiary healthcare facility in Brazil. A cross-sectional study was performed, which included all isolates of confirmed pulmonary TB patients from 2015 to 2018. Both Xpert MTB/RIF and GenoType MTBDR plus assays were performed to detect rifampicin and isoniazid resistance. In addition, isolates with detected resistance to rifampicin and/or isoniazid were analysed by phenotypic testing using MGIT-960 SIRE kit and whole-genome sequencing (WGS) using Illumina MiSeq Sequencing System. 2148 respiratory specimens tested with Xpert MTB/RIF were included: n=1556 sputum, n=348 bronchoalveolar lavage and n=244 gastric washing. The overall Xpert MTB/RIF sensitivity in sputum was 94% and the overall specificity was 98%. The negative predictive value in sputum of all the patients was 99% with a positive predictive value of 89%. The concordance between Xpert MTB/RIF and phenotypic susceptibility test was 94.1%, while its concordance with WGS was 78.9%. Xpert MTB/RIF is a rapid and accurate diagnostic strategy for pulmonary TB, which can contribute to improvement in TB control. However, detection of rifampicin resistance might be associated with false-positive results. Xpert MTB/RIF has the potential to reduce the time to diagnose TB, with high accuracy, including paucibacillary disease. It is also feasible to detect rifampicin resistance, with a high concordance with phenotypic tests and whole-genome sequencing. http://bit.ly/2WW4jmt